NILAI- NILAI SYARIAH DALAM BISNIS - Vera Ayu Oktoviasari (Lembaga Penelitian Dan Pengabdian Masyarakat Institut Agama Islam Sultan Muhammad Syafiuddin Sambas Kalimantan Barat, 2022)
Islam teaches anyone who trades so that there are values ​​that have been prescribed by religion so that business people should be guided by the prevailing Islamic teachings, because in this case sharia business is a business activity carried out by someone based on sharia. Islamic religion, where every method of obtaining and using the assets they get must comply with the rules of the Islamic religion (halal and unlawful). Thus the business being run also gets a blessing. In sharia business, not people who are Muslim also use sharia, but in other religions they also do business according to the sharia listed in each book according to the beliefs held by business people, in other words, if business has been carried out based on values/norms in force so that legally you do not get criminal or other sanctions in the future. Therefore, for adherents of the Islamic religion by applying the business values ​​contained in the principal religion of Islam, practicing the pillars of faith, paying zakat and staying away from usury and everything that is contrary to Islamic law. Rather than that, it is hoped that business people will always pay attention to the principles or values ​​that depend on Islamic law and do business by not committing fraud or things that are detrimental for personal gain, away from usury and closer to Allah SWT.